Cochlear Implantation for Single-Sided Deafness: A New Treatment Paradigm - Zeitler, Daniel M.; Dorman, Michael F. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Unilateral severe-to-profound sensorineural hearing loss (SNHL), also known as single sided deafness (SSD), is a problem that affects both children and adults, and can have severe and detrimental effects on multiple aspects of life including music appreciation, speech understanding in noise, speech and language acquisition, performance in the classroom and/or the workplace, and quality of life. Additionally, the loss of binaural hearing in SSD patients affects those processes that rely on two functional ears including sound localization, binaural squelch and summation, and the head shadow effect. Over the last decade, there has been increasing interest in cochlear implantation for SSD to restore binaural hearing. Early data are promising that cochlear implantation for SSD can help to restore binaural functionality, improve quality of life, and may faciliate reversal of neuroplasticity related to auditory deprivation in the pediatric population. Additionally, this new patient population has allowed researchers the opportunity to investigate the age-old question “what does a cochlear implant (CI) sound like?.”
Keywords: cochlear implant; insertion depth; single-sided deafness; hearing loss; binaural hearing; sound quality; vestibular schwannoma